Numerical Performance Investigation of a Hybrid eCVT Specialized Agricultural Tractor - Francesco Mocera; Valerio Martini (Applied Sciences, 2022)
The need for highly efficient agricultural machineries is increasing the interest of the research community and of industrial manufacturers towards the use of integrated electric systems in combination with traditional powertrain elements. In this work, a hybrid electric tractor with electric continuously variable transmission (eCVT) capabilities was studied to investigate their performance in comparison with that of traditional diesel-powered tractor designs. This hybrid electric configuration can be classified as a power-split architecture that aims to combine the best characteristics of both the simpler parallel and the series hybrid layout while minimizing their main drawbacks. An eCVT configuration can allow for optimizing the diesel operating point with respect to the current working conditions, and achieving peak power performance and energy saving with relatively small electric machines. The proposed hybrid eCVT (HeCVT) tractor architecture was studied using a numerical model that allowed for developing two different control strategies: a charge depleting mode enabling the driver to use full power for the most power-intensive scenarios and a charge sustaining mode developed to optimize efficiency and battery use along an entire work day. To test the proposed architecture, several tasks derived from experimental field measurements on a specialized agricultural tractor were used. HeCVT results were compared with a numerical model of the traditional tractor validated by these experimental data. The HeCVT tractor showed good performance in terms of peak power capabilities using a downsized diesel engine, and consistent fuel savings were obtained according to typical daily working scenarios.